Does Orthopaedic Outpatient Care Reduce Emergency Department Utilization After Total Joint Arthroplasty?. Issue 8 (August 2018) - Chaudhary, Muhammad Ali; Lange, Jeffrey K.; Pak, Linda M.; Blucher, Justin A.; Barton, Lauren B.; Sturgeon, Daniel J.; Koehlmoos, Tracey; Haider, Adil H.; Schoenfeld, Andrew J.
Abstract: Background: Emergency department (ED) visits after elective surgical procedures are a potential target for interventions to reduce healthcare costs. More than 1 million total joint arthroplasties (TJAs) are performed each year with postsurgical ED utilization estimated in the range of 10%. Questions/purposes: We asked whether (1) outpatient orthopaedic care was associated with reduced ED utilization and (2) whether there were identifiable factors associated with ED utilization within the first 30 and 90 days after TJA. Methods: An analysis of adult TRICARE beneficiaries who underwent TJA (2006-2014) was performed. TRICARE is the insurance program of the Department of Defense, covering > 9 million beneficiaries. ED use within 90 days of surgery was the primary outcome and postoperative outpatient orthopaedic care the primary explanatory variable. Patient demographics (age, sex, race, beneficiary category), clinical characteristics (length of hospital stay, prior comorbidities, complications), and environment of care were used as covariates. Logistic regression adjusted for all covariates was performed to determine factors associated with ED use. Results: We found that orthopaedic outpatient care (odds ratio [OR], 0.73; 95% confidence interval [CI], 0.68-0.77) was associated with lower odds of ED use within 90 days. We also found that index hospital length of stay (OR, 1.07; 95% CI, 1.04-1.10), medical comorbidities (OR, 1.16; 95% CI, 1.08-1.24), and complications (OR, 2.47; 95% CI, 2.24-2.72) were associated with higher odds of ED use. Conclusions: When considering that at 90 days, only 3928 patients sustained a complication, a substantial number of ED visits (11, 486 of 15, 414 [75%]) after TJA may be avoidable. Enhancing access to appropriate outpatient care with improved discharge planning may reduce ED use after TJA. Further research should be directed toward unpacking the situations, outside of complications, that drive patients to access the ED and devise interventions that could mitigate such behavior. Level of Evidence: Level III, therapeutic study.